BERAT BADAN BALITA SEBELUM DAN SESUDAH PEMBERIAN MAKANAN TAMBAHAN PEMULIHAN DI BUPATEN BUTON UTARA - Aisnah Aisnah; Wa Ode Salma; Asnia Zainuddin (NHM PRESS, 2022)
The problem of nutrition is one of the determinants of the quality of human resources. Malnutrition will cause failure of physical growth and development of intelligence, reduce body resistance which results in increased morbidity and mortality. This study aims to determine the toddler's weight before and after the provision of Recovery Food Supplement (PMT-P) in North Buton District. This type of research is descriptive observational using a survey design involving 75 mothers under five in the working area of ​​the North Buton District Health Office selected by purposive sampling. The results showed that the body weight before the Recovery Supplementary Food (PMT-P) was bad (100%), the body weight after the Recovery Supplementary Feeding (PMT-P), there were still 23 respondents in the bad category. The conclusion of the study is that there is an increase in the weight of toddlers with growth under the red line after giving additional food for recovery in North Buton Regency.